A descriptive study of children with cerebral palsy at Chris Hani Baragwanath academic hospital - Mahlaba, Ntombizodwa (My University, 2016)
Cerebral Palsy is a motor disability that is due to a non-progressive insult to the motor brain that is still developing. The term thus describes a group of disorders that are due to the insult. The motor disturbances present are often accompanied by seizures together with impairment in sensation, communication, cognition, and perception. There is limited knowledge about the demographics of children with CP seen at Chris Hani Baragwanath Academic Hospital CP clinic, this study was aimed at describing these demographics, to expand on what is currently known about these patients. The study was a retrospective descriptive study of clinic files of new CP patients seen at CP clinic from 1st January to 31st December 2012. The objectives of the study were: to determine the age at presentation; to establish the commonest types of CP seen at the clinic; to determine imaging abnormalities; and to assess the level of functional capabilities of patients using the Gross Motor Functional Classification Scale. The data was collected from 145 patient’s clinic files, and managed using REDCap and a statistical programme: STATA 12.0. 145 patients files were reviewed, 92 were males, 53 were females. The average age at presentation was 34.17 months (2.8 years); most patients had moderate type of CP (46.2%), predominately mixed spastic diplegia (20.7%). The most common imaging modality used was a CT scan (60.7%); it revealed hypoxic ischemic brain injury in 42% of cases. The level of severity as described by the GMFCS was level III in most cases (37.50%). Cerebral palsy is a common, debilitating disorder; this study has highlighted some of the demographics of these patients at Chris Hani Baragwanath Academic Hospital, CP clinic.
A research report Submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the Degree Of Master of Medicine in the branch of Paediatrics. Johannesburg, April 2015